What factors influence the purchase intent of maritime cruise tourists regarding Portuguese souvenirs - de Castro Fernandes Alves, Pedro Filipe (My University, 2024)
This research investigates the factors influencing the purchase intent of maritime cruise tourists regarding Portuguese souvenirs. Utilizing qualitative and quantitative methods, the study examines secondary data from existing literature and primary data collected from a targeted questionnaire. The analysis focused on understanding consumer desires and expectations, identifying gaps and opportunities in the market, and evaluating preferred souvenirs, client satisfaction, quality expectations, and the importance of price. The findings reveal that cruise tourists prioritize authenticity and cultural significance when selecting souvenirs from Portuguese ports. Businesses aiming to cater to this market should emphasize the production and promotion of locally crafted items that encapsulate Portugal's rich heritage. While price is a factor in the purchase decision, it does not dominate tourist choices. Instead, creating memorable experiences and offering high-quality, culturally authentic products are crucial to attracting and satisfying maritime cruise tourists. By addressing these factors, businesses can better align their offerings with tourist preferences, enhancing both customer satisfaction and sales. This study contributes to the understanding of tourist behavior in the maritime cruise sector and provides actionable insights for souvenir producers and retailers in Portugal.

Esta pesquisa investiga os fatores que influenciam a intenção de compra dos turistas de cruzeiros marítimos em relação aos souvenirs portugueses. Utilizando métodos qualitativos e quantitativos, o estudo examina dados secundários da literatura existente e dados primários recolhidos a partir de um questionário direcionado. A análise concentrou-se em entender os desejos e expectativas dos consumidores, identificando lacunas e oportunidades no mercado, avaliando souvenirs preferidos, satisfação dos clientes, expectativas de qualidade e a importância do preço. Os resultados revelam que os turistas de cruzeiros priorizam a autenticidade e o significado cultural ao selecionar souvenirs nos portos portugueses. As empresas que pretendem atender a esse mercado devem enfatizar a produção e promoção de itens artesanais locais que encapsulem o rico património de Portugal. Embora o preço seja um fator na decisão de compra, ele não domina as escolhas dos turistas. Em vez disso, criar experiências memoráveis e oferecer produtos de alta qualidade e culturalmente autênticos são cruciais para atrair e satisfazer os turistas de cruzeiros marítimos. Ao abordar esses fatores, as empresas podem alinhar melhor suas ofertas às preferências dos turistas, melhorando tanto a satisfação do cliente quanto as vendas. Este estudo contribui para a compreensão do comportamento dos turistas no setor de cruzeiros marítimos e fornece insights acionáveis para produtores e retalhistas de souvenirs em Portugal.
Keywords: Marine Cruise Tourism; Souvenirs; Purchase Intent; Tourist Preferences; Cultural Authenticity